Indicators of English Proficiency: A Structural-Semiotic Analysis of Self-Presentation in “English with Lucy” and Its Educational Implications - Tatan Tawami; Eddy Soeryanto Soegoto; Retno Purwani Sari; Thomas Chochole; Chepi Nur Albar; Senny Luckyardi (International Journal of Language Education, 2026)
This study examined how popular social media influencers construct English proficiency as a key aspect of self-presentation and explored its implications for English learning. This study used a qualitative approach with structural semiotic analysis, and it investigated how influencers communicate English proficiency through visual and textual elements. The findings highlighted a growing need for critical language awareness among learners because influencers often reinforce standard language ideologies and idealized notions of “proper” English. Additionally, the study underscored the importance of integrating multimodal literacy into language education, given the increasingly multimodal nature of contemporary communication. In conclusion, encouraging students to examine their semiotic choices when engaging with English online critically fosters greater self-awareness in digital interactions, enabling them to navigate linguistic diversity and authenticity in virtual spaces. Ultimately, this research contributes to a profound understanding of how English proficiency is socially constructed in today’s media landscape.